2019
DOI: 10.3389/fpsyg.2019.01038
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Investigating the Effect of Music-Based Intervention on Depression and Anhedonia

Abstract: This study investigated the effect of a music-based intervention on depression and associated symptoms. Twenty individuals formally diagnosed with Major Depressive Disorder and in a current Major Depressive Episode (11 females and 8 males; aged between 26 and 65 years) undertook a 5 weeks intervention consisting of music listening combined with rhythmic sensory stimulation. Participants listened to a set of designed instrumental music tracks embedded with low-frequency sounds (30–70 Hz). The stimuli were deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 114 publications
(141 reference statements)
1
17
0
Order By: Relevance
“…Our meta‐analysis results were based on large populations; thus, implications for the clinical setting are that symptoms of depression in patients with breast cancer may be alleviated with the use of art therapies. Depressive symptoms include diminished interest, cognitive dysfunction and sleep disorders (Braun Janzen, Al Shirawi, Rotzinger, Kennedy, & Bartel, 2019). A previous meta‐analysis (Boehm et al., 2014) ( covering four studies on anxiety and five on depression) suggested that art therapy has beneficial effects on anxiety but not on depression in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our meta‐analysis results were based on large populations; thus, implications for the clinical setting are that symptoms of depression in patients with breast cancer may be alleviated with the use of art therapies. Depressive symptoms include diminished interest, cognitive dysfunction and sleep disorders (Braun Janzen, Al Shirawi, Rotzinger, Kennedy, & Bartel, 2019). A previous meta‐analysis (Boehm et al., 2014) ( covering four studies on anxiety and five on depression) suggested that art therapy has beneficial effects on anxiety but not on depression in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although not a rigorously controlled study and not measuring changes in the vagal tone, the pilot study did find a reduction in depression scores in the treatment group and attributes this to stimulation of the vagus nerve and the central nervous system through the abdomen. A study by Braun Janzen et al [ 89 ] that applied a very similar treatment also found a reduction in depression and anhedonia although it did not premise vagal stimulation.…”
Section: Neurological Effectsmentioning
confidence: 99%
“…Assuming then that vibratory stimulation (RSS) can drive oscillatory coherence and potentially regulate dysrhythmic circuits in the brain, RSS may employ the mechanism of oscillatory coherence and positively affect the health conditions resulting to some extent from these dysrhythmias. The positive response of major depression to RSS may be an indicator of this [ 89 ]. The mechanism of driving oscillatory coherence with RSS broadens the focus from the neuroscience of circuit connections (the connectome) to the framework of dynamic brain rhythms related to neural spiking activity (the dynome) [ 13 ].…”
Section: Neurological Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, researchers began to consider whether rewards can be used as a positive emotional stimulus to have an effect on depression, many studies have begun to study the effect of reward intervention on depressive symptoms. Music interventions can improve the quality of sleep, quality of life, and lack of pleasure in patients (13)(14)(15). What is more, encouraging patients to participate in reward activities during treatment was found to be effective in reducing MDD symptoms (16), and positive social feedback can change mood levels and reward the value of neutral faces (17).…”
Section: Introductionmentioning
confidence: 99%